Essential Role of Sox2 for the Establishment and Maintenance of the Germ Cell Line123. (5th July 2013) - Campolo, Federica; Gori, Manuele; Favaro, Rebecca; Nicolis, Silvia; Pellegrini, Manuela; Botti, Flavia; Rossi, Pellegrino; Jannini, Emmanuele A.; Dolci, Susanna
Abstract Sox2 is a pluripotency‐conferring gene expressed in primordial germ cells (PGCs) and postnatal oocytes, but the role it plays during germ cell development and early embryogenesis is unknown. Since Sox2 ablation causes early embryonic lethality shortly after blastocyst implantation, we generated mice bearing Sox2‐conditional deletion in germ cells at different stages of their development through the Cre/loxP recombination system. Embryos lacking Sox2 in PGCs show a dramatic decrease of germ cell numbers at the time of their specification. At later stages, we found that Sox2 is strictly required for PGC proliferation. On the contrary, Sox2 deletion in meiotic oocytes does not impair postnatal oogenesis and early embryogenesis, indicating that it is not essential for oocyte maturation or for zygotic development. We also show that Sox2 regulates Kit expression in PGCs and binds to discrete transcriptional regulatory sequences of this gene, which is known to be important for PGCs survival and proliferation. Sox2 also stimulates the expression of Zfp148, which is required for normal development of fetal germ cells, and Rif1, a potential regulator of PGC pluripotency. STEM Cells2013;31:1408–1421